Kesejahteraan Subjektif Pada Anak YatimDi Panti Asuhan Yatim Muhammadiyah Purworejo - Wafa, Zulfa Annisa; , Drs. M. Najmuddin Zuhdi M.A; , Dr. Wiwien Dinar Pratisti M.Si (2016)
Orphanage is a place of service for orphans to obtain a good education and care as a good alternative. Their ucation and care is under the guidance of the care made orphans must live in the orphanage in order to get the full care by the board orphanage. With the obligation to stay away from parents, education is mandatory in the orphanage to make children experience various things that affect well-being. This study aims to understand (in depth) and describe the subjective well-being of orphans in orphanages orphaned Muhammadiyah Purworejo. This study uses a henomenological study using a qualitative approach. The subjects were teenagers who lived in the orphanage, six people at the age of 17 years with 3 female and 3 male gender to male. This study uses data collection interview. Results from this study showed that orphans Orphanage Yatim Muhammadiyah Purworejo measured by physical kebutuhn compliance, and the need affection orphans. Based on this it is known that most feel better due to physical needs have been met, such as education of religious knowledge, patterns of life of independence are applied in homes. Orphans who have felt prosperous stay at home due to need their love needs of the family. The factors that affect well-being is the mind, education, employment, economy, personality, enthusiasm for learning, social support of family, friends and the community. Non-formal education in the orphanage in the form of religious education for the welfare of more influential since acquiring religious knowledge orphans become more understanding of the rules of Islam, accept the circumstances of life, add to the faith and teaching in different homes with at home. Keywords: Well-Being, orphans, orphanages, education